Public demand and optimization of smart government service platform from the perspective of service life cycle based on the Kano model: A Chinese case study. - Yang Zhu; Yifan Peng; Lingling Xin; Xiao Zhang (PLoS ONE)
Background Smart government is an effective way to promote government innovation and public services. However, in China, there is a mismatch between the development of smart government service platform and the demands of the public. Therefore, this study aims to clarify the categories and priorities of public demands in smart government services from service life cycle perspective. Methods Based on the service life cycle perspective, 29 public demands in government services were summarized. A self-designed questionnaire was designed and distributed to the public using the "Jingtong" smart government service platform in Beijing. Based on 648 valid questionnaires collected, the Kano model was used to analyze the category attributes of demands, and the traditional classification and other two coefficient analysis methods were used to prioritize the demands. Results The analysis of the collected questionnaires shows that personal privacy should be prioritized as it is the prerequisite for the widespread use of smart government services. Then, one-dimensional quality and attractive quality should be satisfied such as decision-making and intelligent scheduling demands, as they are central to the capability leap of smart government services. Additionally, must-be quality should be satisfied such as information sharing demand, as they are foundation of smart government services. Lastly, the quick response demand should be transformed into other demand types. Conclusions This study analyzes public demands at various stages from the perspective of the service life cycle, based on the prioritization of demands, proposes targeted optimization strategies for smart government service platform in the guide, interaction, processing, and evaluation periods. This provides important references for the overall construction of smart government.